2013
DOI: 10.2478/s11756-013-0161-y
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species and seed germination

Abstract: Reactive oxygen species (ROS) are continuously produced by the metabolically active cells of seeds, and apparently play important roles in biological processes such as germination and dormancy. Germination and ROS accumulation appear to be linked, and seed germination success may be closely associated with internal ROS contents and the activities of ROS-scavenging systems. Although ROS were long considered hazardous molecules, their functions as cell signaling compounds are now well established and widely stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 62 publications
3
88
0
Order By: Relevance
“…Reactive oxygen species (ROS) are considered toxic molecules formed during normal metabolic functions and induced when plants are exposed to environmental stimuli (Éaux and Toledano, 2007). However, they also act as signaling molecules in response to different stresses during germination (Gomes and Garcia, 2013;Tenhaken, 2015) or even germination under normal conditions, as occurs in Dalbergia nigra seeds (Matos et al, 2014). Reactions catalyzed by peroxidase also result in stimulation of sprouting, especially in the weakening of the cell wall, since they produce the hydroxyl radical (Richards et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species (ROS) are considered toxic molecules formed during normal metabolic functions and induced when plants are exposed to environmental stimuli (Éaux and Toledano, 2007). However, they also act as signaling molecules in response to different stresses during germination (Gomes and Garcia, 2013;Tenhaken, 2015) or even germination under normal conditions, as occurs in Dalbergia nigra seeds (Matos et al, 2014). Reactions catalyzed by peroxidase also result in stimulation of sprouting, especially in the weakening of the cell wall, since they produce the hydroxyl radical (Richards et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, it was suggested that reactive oxygen species ROS are also related to various aspects of plant physiology, such as dormancy and germination 1,2 . It is, thus, possible that ROS, along with plant hormones, constitutes an alternative form of regulation of plant physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Superoxide dismutase, catalase, and peroxidase are enzymes that eliminate free radicals and peroxides, as well as malate dehydrogenase, acid phosphatase, and glutamate dehydrogenase, which are indicative of deterioration, since they are involved in cell metabolism (Taveira et al, 2012). Thus, information on the activity of certain enzymes can be used in studies on seed deterioration (Gomes;Garcia, 2013). Taveira et al (2012), studying the protein profile of coffee seeds dried under different methods, observed greater activity of the catalase enzyme in seeds of worse physiological performance.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, membrane function is changed, which provokes lipid peroxidation, degradation of nucleic acids, and inactivation of enzymes (Garg;Manchanda, 2009). Reduction in the activity of scavenger enzymes increases the sensitivity of seeds to oxidative stress (Gomes;Garcia, 2013). Superoxide dismutase, catalase, and peroxidase are enzymes that eliminate free radicals and peroxides, as well as malate dehydrogenase, acid phosphatase, and glutamate dehydrogenase, which are indicative of deterioration, since they are involved in cell metabolism (Taveira et al, 2012).…”
Section: Resultsmentioning
confidence: 99%